Factors influencing consumer’s intention towards online grocery shopping - Sulastri, Anis Shaira; Mohd Nawi, Nolila; Abdullah, Amin Mahir; Abd Latif, Ismail (International Organization of Scientific Research, 2017)
Online platform nowadays has started to replace the traditional market and require consumers to change their buying habits and patterns extensively. Thus, the trend of having grocery delivered to the doorstep has been introduced to Malaysian consumers especially who lives in urban area. Previous studies have shown that online groceries are not consistently purchased by the consumers due to several reasons such as inconsistent quality and lack of sensory characteristics. However, there are still number of consumers who continuously shops groceries through online platform. Thus, the aim of this study is to determine factors influencing consumer’s intention to shop groceries online. The primary data were collected using structured questionnaire in the form of online survey with 521 respondents in Klang Valley, Malaysia. Data collected were analyzed using descriptive analysis and factor analysis. The findings of the study showed that majority of the online grocery shoppers are female with the age ranged between 26-35 years old. Besides that, results from factor analysis revealed that perceived usefulness, satisfaction, perceived risk, perceived information accessibility and perceived ease of use are among factors that influenced consumer’s intention towards online grocery shopping. Therefore, this study can be used to assist online grocery retailers to formulate effective strategies to gain more consumers’ confidence to make use of online grocery shopping.